In situ synthesis of CoFe-LDH on biochar for peroxymonosulfate activation toward sulfamethoxazole degradation: cooperation of radical and non-radical pathways. (1st February 2023) - Fu, Manjun; Yan, Juntao; Chai, Bo; Fan, Guozhi; Ding, Deng; Song, Guangsen
Abstract : The BC/Co1 Fe1 -LDH-4 composite exhibited an outstanding PMS activation performance for SMX degradation with both radical and non-radical pathways being involved. Abstract : Developing an efficient, low-cost and stable catalyst to activate peroxymonosulfate (PMS) for pollutant degradation is crucial in environmental remediation. Herein, Co1 Fe1 layered double hydroxide (Co1 Fe1 -LDH) was in situ loaded on biochar (BC) derived from rape straw for sulfamethoxazole (SMX) degradation via activating PMS. It could be found that the optimal catalyst (BC/Co1 Fe1 -LDH-4) exhibited the highest SMX degradation efficiency of 94.8% within 5 min reaction, far more than pristine Co1 Fe1 -LDH (58.5%), which might be ascribed to the synergistic effects between Co1 Fe1 -LDH and BC during the reaction. For one thing, BC itself participated in the catalytic degradation reaction as an activator and made the catalyst have excellent adsorption and degradation performance. For another, BC as a carrier not only effectively inhibited the agglomeration of Co1 Fe1 -LDH to increase the active sites, but also accelerated the Co 2+ /Co 3+ and Fe 2+ /Fe 3+ cycles to reduce the leaching of metal ions. Meanwhile the leaching of trace metal ions also promoted the degradation of SMX to a certain extent, indicating that the catalytic mechanism was a combination of homogeneous and heterogeneous catalysis, and the latter was dominant. The quenching trials, electron paramagnetic resonance (EPR) and electrochemical measurements implied that the radical and non-radical processes were involved in the reaction, where SO4 ˙ −, ˙OH and O2 ˙ − were the main radical species to drive the radical process, and 1 O2 and direct electron transfer were responsible for the non-radical process. In addition, the possible SMX degradation pathways were reasonably proposed by high-performance liquid chromatography-mass spectrometry (HPLC-MS) tests and the SMX mineralization degree was provided through total organic carbon (TOC) measurements. This present work provides new insight into the construction of highly efficient PMS activation catalysts for environmental wastewater treatment.